Analisis Forensik Digital pada Aplikasi Twitter di Android sebagai Bukti Digital dalam Penanganan Kasus Prostitusi Online - Pratama, Sang Putu Febri Wira; Putra, I Gusti Ngurah Anom Cahyadi; Hamid, Muhammad Akbar; Christian, Calvin; Merdana, I Ketut Kusuma (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
At this time the use of social media from time to time has experienced rapid development, one of which is the social media twitter. Twitter social media has many benefits such as making tweets about daily activities. However, Twitter social media has a negative side in its use, one of which is online prostitution. Prostitution is an act of cyber crime that violates the rules and norms that exist in society. Therefore, to overcome these cyber crimes, the necessary action is to review online prostitution on Twitter social media. In this study, a digital forensic analysis was conducted on Twitter social media on smartphones related to acts of prostitution using the National Institute of Justice (NIJ). Based on the research conducted, digital evidence is obtained that can be accounted for by the perpetrators.